Characteristics of Buffalo Production and Research Systems in Southern Mexico - de la Cruz-Cruz, Luis Alberto; Roldán-Santiago, Patricia; Berdugo-Diaz, Daniel Fernando; Rodríguez-Florentino, René; Berdugo-Gutiérrez, Jesús Alfredo (Journal of Buffalo Science, 2022)
Background: This research aimed to characterize the production units of water buffalo (Bubalus bubalis) and review the published scientific literature in southeastern Mexico. Methods: Between May and June 2020, a questionnaire was created in Google forms, distributed through social networks, and emailed to buffalo breeders. In addition, a review of different scientific databases on the experimental studies developed in Mexico on buffalo was performed. Results: Data was collected from 8,867 animals from 13 producers located in southeastern Mexico; dual-purpose (milk-meat) is the primary zootechnical purpose (69.24%), and the rest is meat production. The buffalo herd is mainly composed of females (72.09%). Females are used primarily to repopulate the herd and males for meat production. Mortality in adults remained between 2 to 5%. 30.76% of the producers produce milk (495 females) with 5.1 L/d on average. 100% of the producers stated that they transform the milk into dairy products, mainly cheeses and other products. In the case of meat production, 31.97% of the males are fattened based on pastures with a weight range between 400-600 kg at the age of 22 months (range 18-30 months). Between 2012-and 2021, 19 studies related mainly to herd health (63.15%) were registered. Conclusion: It is concluded that this Mexican species has great productive potential with different areas for improvement. Due to sanitary management and rusticity, mortality is low. It is necessary to develop other lines of research associated with the reproduction, production of milk/meat, health, quality of products, safety, and sustainability of buffalo activity in Mexico.